IoT-Based Shoe for Enhanced Mobility and Safety of Visually Impaired Individuals - Singh, Bakshish; Ekvitayavetchanuku, Pongkit; Shah, Bharti; Sirohi, Neeraj; Pundhir, Prachi (EAI Endorsed Transactions on Internet of Things, 2024)
This research paper presents the design, development, and evaluation of an Internet of Things (IoT)- based shoe system to enhance the mobility and safety of visually impaired individuals. The proposed shoe leverages IoT technologies, embedded sensors, and wireless communication to provide real-time information and assistance to blind individuals during their daily activities. The system encompasses a wearable shoe device equipped with sensors, a microcontroller unit, and a companion mobile application that relays important data and alerts the user. The effectiveness of the IoT-based shoe is evaluated through a series of user tests and feedback surveys. The results demonstrate the potential of this innovative solution to empower blind individuals, improve their independence, and promote a safer environment for their navigation.
Keywords: Internet of Things; IoT technologies; embedded sensors; microcontroller; navigation; blind individuals